The Influence of Popular Culture on the F&B Products in TikTok Content - Kristina, Mira; Budiwaty, Suci (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This research aimed to identify the characteristics of popular culture used in the content of F&B products on TikTok based on John Storey's theory and also the influence of popular culture on F&B products. The TikTok video contents were the F&B products: Mixue, McDonalds, and Starbucks. The videos were from 2022 until 2023. Documentation techniques were used in collecting the data and information supporting the analysis. This research used a descriptive qualitative method. The result of the analysis showed that the F&B products were following the six characteristics of popular culture, there are 3 data found that Popular culture is widely liked by many people, 3 data found that Popular culture is to say that it is a culture that remains after we have decided what high culture is, 4 data found that Popular culture is referred to as 'mass culture', 3 data found that Popular culture is a culture that comes from the 'people', 6 data found that Popular culture as a place of struggle between the 'resistance' of subordinate groups and the 'aggregation' forces that operate in the interests of the dominant group, and 6 data found that Popular culture is a culture of postmodernism. Popular culture also influences peoples eating habits through F&B products. People become consumptive and they buy things not for necessity, but only for their satisfaction.